Changes in vitamin D status among adults from the COVID-19 pandemic to post-pandemic normality - Chen, Yanzhao; Kong, Guilian (Frontiers in Nutrition, 2024)
To investigate the impact of the COVID-19 pandemic on vitamin D status among adults. A total of 1525 adults from Henan Provincial People's Hospital were included. The results revealed a significant difference in overall 25-hydroxyvitamin D (25(OH)D) levels between 2022 [18.14, 13.78, 23.68] and 2023 [19.15, 14.88, 25.01, p=0.004]. Notably, males exhibited a substantial difference in 25(OH)D levels, 18.01 [14.10, 23.53] in 2022 and 20.49 [16.11, 26.01] in 2023 (p<0.001). The prevalence of vitamin D deficiency was significantly higher in 2022 (62%) compared to 2023 (54.9%, p=0.009), with males having higher rates of deficiency (64.1% in 2022 and 47.2% in 2023). These findings were supported by an independent cohort of 168 individuals tested in both years, showing overall 25(OH)D levels of 20.73 ± 9.37 in 2022 and 22.28 ± 8.59 in 2023 (p=0.012), and vitamin D deficiency rates of 58.3% in 2022 and 47.0% in 2023 (p=0.038). In the 40-49 age group, 25(OH)D levels were significantly lower in 2022 [16.10, 12.41, 21.18] compared to 2023 [18.28, 13.91, 23.86, p=0.005], with a higher vitamin D deficiency rate in 2022 (72.8%) compared to 2023 (59.9%, p=0.02). Furthermore, in February, March, and April, 2022, 25(OH)D levels were significantly lower compared to 2023 (p<0.001, p=0.002, p<0.001, respectively), accompanied by a higher prevalence of vitamin D deficiency (p<0.001, p=0.015, p<0.001, respectively). In conclusion, our study findings indicate an elevated prevalence of vitamin D deficiency among the adult population, with particular emphasis on adult males, during the course of the COVID-19 pandemic.